Advanced Clock Tree Synthesis Optimization: A Multi-Source Approach to Minimizing Skew and Power in Sub-7nm ASIC Designs - Ramalinga Reddy Kotapati (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Clock tree synthesis (CTS) optimization remains a critical challenge in advanced node ASIC physical design, particularly as semiconductor technologies continue to scale down. This article presents a comprehensive methodology for optimizing multi-source clock distribution networks while addressing power consumption and timing accuracy concerns. The article introduces an integrated approach that combines functional clock gating strategies with sophisticated skew management techniques to achieve optimal performance in high-frequency designs. The proposed framework incorporates latch-based timing analysis to effectively handle setup and hold time violations while implementing selective buffer optimization to reduce dynamic power consumption. The methodology demonstrates significant improvements in power efficiency and timing closure compared to conventional approaches. The experimental results, validated across multiple test cases in advanced technology nodes, show marked reductions in clock insertion delay and substantial improvements in skew variation tolerance. This article provides valuable insights for physical design engineers working on next-generation semiconductor devices, particularly in applications requiring stringent power and performance specifications.